2014
DOI: 10.1103/physreva.90.033846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multimode entanglement on lossy optical quantum metrology

Abstract: In optical interferometry multimode entanglement is often assumed to be the driving force behind quantum enhanced measurements. Recent work has shown this assumption to be false: single-mode quantum states perform just as well as their multimode entangled counterparts. We go beyond this to show that when photon losses occur, an inevitability in any realistic system, multimode entanglement is actually detrimental to obtaining quantum enhanced measurements. We specifically apply this idea to a superposition of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…There are works in the literature which discuss the unnecessity of mode entanglement [5,39,40,50,53,55,96,97]. Note, however, that in those works the probe states are not restricted to Gaussian states and in addition just the achievability of the Heisenberg scaling (quadratic in N ) is discussed.…”
Section: Discussionmentioning
confidence: 99%
“…There are works in the literature which discuss the unnecessity of mode entanglement [5,39,40,50,53,55,96,97]. Note, however, that in those works the probe states are not restricted to Gaussian states and in addition just the achievability of the Heisenberg scaling (quadratic in N ) is discussed.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that in a multimode (multipath) interferometer, measuring all phases simultaneously with a mode-entangled state can enhance the precision [9]. However, in stark contrast to this, in other applications of quantum metrology multimode entanglement can be detrimental, such as when measuring coupled phases [12] or when loss is considered [13]. Furthermore, from a practical point of view, large multimode-entangled states are notoriously difficult to produce and are fragile to experimental imperfections and photon losses.…”
Section: Introductionmentioning
confidence: 93%
“…However, the practical realization of quantum metrology is limited by the ubiquitous decoherence effect induced by the influence of outer environments [27][28][29][30][31][32][33][34][35][36][37][38], which causes entanglement degradation to quantum systems. This inspires the emergence of open-system quantum metrology [39,40].…”
Section: Introductionmentioning
confidence: 99%